A Test of Transformational and Transactional Leadership Styles on Employees' Satisfaction and Performance in the UAE Banking Sector - Awamleh, Raed; Evans, John; Mahate, Ashaf (Journal of Comparative International Management)

(untitled) (Management Futures, 2005)
Abstract This study tested the transformational leadership theory among managers at functional levels in United Arab Emirates (UAE) banks. The UAE banking sec-tor was chosen due to its importance in the U.A.E. economy and its significant contribution to the Emirates GDP. The paper examines the effects of both transformational and transactional leadership styles of bank managers/supervisors on employees' satisfaction and self-perceived performance. Self-esteem and leadership disposition (Romance of Leadership) of employees were hypothe-sized to act as moderators. Data was collected from employees working in national and international banks operating in the UAE. A multiple regression analysis indicated that transformational leadership style and self-esteem were related to job satisfaction. On the other hand, transformational leadership, Romance of Leadership (RLS), and self-esteem were all related to self-perceived performance. Results confirmed that to elicit higher levels of satisfac-tion and performance among bank employees, managers/supervisors need to demonstrate transformational leadership attributes.